Mixed Heritage: The Formation of Ethnic Identity among Biracial Adolescents in Indonesia - Soemantri, Nathalia Perdhani; Said, Mashadi; Anggraeni, Diana; Diharjo, Helena Lodya Haryani; Paccagnnelae, Nalendra (Advances in Social Sciences Research Journal, 2025)
This study aims to identify and analyse the process of ethnic identity formation among biracial adolescents in Indonesia within the context of intercultural communication. A descriptive qualitative approach was employed, using in-depth interviews with three participants of mixed ethnic backgrounds: Indonesian–American, Indonesian–Japanese, and Indonesian–Arab. Data analysis followed the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings reveal five major themes: (1) early awareness of ethnic identity through family socialization and religious traditions; (2) identity negotiation in social environments that often generate physical and ethnic stereotypes; (3) integration of cross-cultural values that create a unique pattern balancing global and local identities; (4) language and family humour as emotional symbols reinforcing ethnic attachment and pride; and (5) dual identity as social capital that expands relational networks and enhances intercultural communication competence. This study emphasizes that dual identity is not a burden but a cultural and social asset that enriches adolescents’ experiences in multicultural societies. The findings highlight the importance of the family, school, and community in creating inclusive social environments that support the development of positive ethnic identity among biracial adolescents. Future research is recommended to extend the geographical scope and examine the role of digital media in shaping ethnic identity among younger generations.